Fair Legal Measures: Addressing Cybercrime Through a Juridical Lenss in Cases of Online Fraud - Ollifia Az Zahra Ainur Islamy; Taufiq Nugroho (Mimbar Keadilan, 2024)
The widespread misuse of information technology is deeply concerning to society due to the prevalence of cybercrime. Cybercrime is a violation of the law by using social networks or the internet as a means of crime, obtaining data illegally, taking advantage and enriching oneself. Online selling business is one of several possibilities for online fraud. This research examines decision number 177/Pid.Sus/2021/PN Smn, specifically focusing on the application of Article 45A paragraph (1) in conjunction with Article 28 paragraph 1 of Law No. 19/2016. This study aims to determine the judge's consideration based on the above decision and the application of sanctions in accordance or not with the relevant article. The source is secondary data using research that is basically doctrinal or normative, case and legislative approaches. The defendant, Juari alias Johan Bin Djun Hie, has been legally found to meet the requirements outlined in the mentioned article of the decision. The panel of judges considered the facts presented, the prosecutor's indictment, the defendant's statement, the testimony of witnesses, and the submitted evidence when deciding on the case. The application of the witnesses is in accordance with the Article mentioned. The Defendant is subject to a maximum prison sentence of 6 years and/or a maximum fine of Rp. 1,000,000,000.00. The legal system must adapt to technological advancements to maintain its efficacy in enforcing the law. Lastly, ongoing crime prevention efforts involve a holistic approach, including public education, cyber security infrastructure development, and collaboration between public and private sectors. This multifaceted approach is essential for the legal system to effectively address the challenges posed by cybercrime in the digital era.